PERAN INOVASI PRODUK DALAM MEMEDIASI PENGARUH ORIENTASI PASAR TERHADAP KINERJA PEMASARAN - Arimbawa, Dyah Jayanti; Jatra, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
One of the SME industrial units that is currently developing and is in great demand by the public today is the coffee industry, along with the large consumption of coffee in Indonesia. North Kuta District is one area that has felt the impact of the development of the coffee shop business. The increasing number of coffee shop developments makes competition between similar businesses higher so that good and optimal marketing performance is needed in maintaining business. This study aims to explain the role of product innovation in mediating the effect of market orientation on marketing performance at coffee shops in North Kuta District. The number of samples in this study were 100 respondents with purposive sampling method. Data collection through the distribution of questionnaires (google form). Data analysis using path analysis techniques. The results showed that market orientation had a positive and significant effect on marketing performance, market orientation had a positive and significant effect on product innovation, product innovation had a positive and significant effect on marketing performance and product innovation could mediate the effect of market orientation on marketing performance